2020
DOI: 10.1002/jgh3.12431
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic retroperitoneal fibrosis diagnosed by endoscopic ultrasonography‐guided fine‐needle biopsy

Abstract: We demonstrate a case, in which endoscopic ultrasonography‐guided fine‐needle biopsy (EUS‐FNB) was useful for determining the diagnosis of lesions of retroperitoneal fibrosis. In our case, accessing the retroperitoneal lesions by conventional percutaneous biopsy procedures was not feasible due to the difficulty of avoiding the inferior vena cava and ureter. We believe that our case demonstrates a unique approach for performing histological analysis in a challenging case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…However, we herein showed that the endoscopic arena is likely to also play a significant role in this setting, which could be even preferred over other modalities. Although isolated reports, that share our positive experiences, exist [17,18,19], EUS-FNA/FNB as a modality for diagnosing RPF has attracted surprisingly little attention in the literature. ▶ Table 1 provides an overview over previously published case reports that demonstrated the use of EUS-FNA/FNB to successfully diagnose RPF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we herein showed that the endoscopic arena is likely to also play a significant role in this setting, which could be even preferred over other modalities. Although isolated reports, that share our positive experiences, exist [17,18,19], EUS-FNA/FNB as a modality for diagnosing RPF has attracted surprisingly little attention in the literature. ▶ Table 1 provides an overview over previously published case reports that demonstrated the use of EUS-FNA/FNB to successfully diagnose RPF.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, open surgery is relatively time-consuming and may be connected to longer hospitalization time. A CT-guided biopsy, on the other hand, is less invasive but considered challenging owing to the considerable depth of lesions and difficulty in avoiding the inferior vena cava and ureters [5,18]. In light of this fact, EUS-FNA/FNB shows greater promise, as, thanks to its transduodenal approach, lesions are easier to reach, which provides a good chance of successful and sufficient tissue collection.…”
Section: Discussionmentioning
confidence: 99%
“…EUS‐FNB is useful for the histological diagnosis of type 1 autoimmune pancreatitis in patients with IgG4‐RD 4 . A previous report described a similar case of idiopathic retroperitoneal fibrosis diagnosed by EUS‐FNB 5 . EUS‐FNB should be considered when percutaneous biopsy is not feasible.…”
Section: Brief Explanationmentioning
confidence: 99%